Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

A friend of mine asked me to help with this problem. I tried induction, but I didn't know how to get this formula.

If $x$ and $y$ are real numbers such that $xy= ax+by$. Show that $$ x^ny^n=\sum_{k=1}^{n}{2n-1-k \choose n-1}(a^n b^{n-k}x^k+ a^{n-k}b^n y^k), \forall n \geq 0 $$

Any help is appreciated.

share|cite|improve this question
How is this related to computer science? – Antonio Vargas Apr 14 '12 at 18:34
It is a question from "Concrete Mathematics, A Foundation for Computer Science". – yaa09d Apr 14 '12 at 18:42
I removed the (computer-science) tag. – user2468 Apr 14 '12 at 18:43
I'm doubtful about the validity of the equation for $n=0$, but that's a minor nitpick. – hardmath Apr 14 '12 at 19:30

$1=\frac{b}{x}+\frac{a}{y}$. So, let $s=\frac{b}{x}, t=\frac{a}{y}$. It is enough to show that $$2=\sum_{k=-\infty}^n \binom{2n-1-k}{n-1}( s^n t^{n-k}+s^{n-k} t^n).$$ Now, let $m=n-k$. Then $$ RHS= (st)^n \sum_{m=0}^{\infty} \binom{n-1+m}{m} (s^{m-n}+t^{m-n})=2.$$ Note that $$(1-z)^{-n}=\sum_{m=0}^{\infty} \binom{n-1+m}{m} z^m.$$

share|cite|improve this answer
Thanks. But Why is the LHS of the first identity is $2$, and why does the sum start from $-\infty$ – yaa09d Apr 15 '12 at 5:54

Hint : Replace $(xy)^n$ (LaTeX notation) on the left by $(ax+by)^n$ expand the left-hand side using the Newton formula, and replace products $x^i y^j$ by $(ax+by)^{min(i,j)},$ etc. Nice exercice !

share|cite|improve this answer
Thanks for the hint. But how can I shorten the expression after that? – yaa09d Apr 14 '12 at 19:53

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.